2021
DOI: 10.1016/j.psj.2020.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of benzoic acid on production performance, egg quality, intestinal morphology, and cecal microbial community of laying hens

Abstract: This study was conducted to determine the effects of supplemental dietary benzoic acid on production performance, egg quality, intestinal morphology, and intestinal microbiota of laying hens. A total of seven hundred twenty 45-wk-old Lohman pink-shell laying hens were randomly allocated to 3 dietary treatments: control ( CON ), diet supplemented with 1,000 mg/kg benzoic acid ( BA1 ), and 2,000 mg/kg benzoic acid ( BA2 ). Each treatment includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
4
21
0
2
Order By: Relevance
“…Correlation analysis revealed the relationship between production performance, gut immune function, and intestinal microorganisms, and clarified the potential roles of intestinal microorganism structure in the production performance and gut immune functions of laying hens. It was worth noting that an increase in Bacteroides abundance was accompanied by the improvements of albumen height, which was also discovered in previous studies [72]. Bacteroides is widely regarded as one of the beneficial genera, which is an effective degraders of nondigestible carbohydrates and SCFA producers, and plays an important role in the maturation of the immune system [73].…”
Section: Discussionsupporting
confidence: 58%
“…Correlation analysis revealed the relationship between production performance, gut immune function, and intestinal microorganisms, and clarified the potential roles of intestinal microorganism structure in the production performance and gut immune functions of laying hens. It was worth noting that an increase in Bacteroides abundance was accompanied by the improvements of albumen height, which was also discovered in previous studies [72]. Bacteroides is widely regarded as one of the beneficial genera, which is an effective degraders of nondigestible carbohydrates and SCFA producers, and plays an important role in the maturation of the immune system [73].…”
Section: Discussionsupporting
confidence: 58%
“…Over the past years, a significant improvement in poultry production has resulted in extremely high level of efficiency in both broiler chickens and laying hens, with birds reaching 3 kg in body weight at 40 days of age and hens laying 500 eggs in 100 weeks (2). The microbiota is defined as the microbial community, including commensal, symbiotic and pathogenic microorganisms (3) which could interact with the host, resulting in the influence on metabolism, immunity and even behavior (4,5). A normal and stable microbiota play a pivotal role in maintaining optimal gastrointestinal functionality, animal health, welfare and production performances (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, our study used this compound that composed of benzoic acid, EOs, and Enterococcus faecium and found that the BEC group had no effect on the production performance of laying hens, but the BEC +challenge group increased laying rate and decreased the FCR of laying hens. It is reported that dietary supplementation with benzoic acid has no effect on the laying rate, feed intake, feed conversion ratio of laying hens ( Gong et al., 2021 ). Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Benzoic acid was considered as one of the most common acidifiers, and it was improved that could increase the weight gain and feed conversion rate of broilers ( Jozefiak et al., 2007 ). Moreover, some studies suggested that benzoic acid had the potential to improve growth and intestinal health ( Partanen and Mroz, 1999 ; Mroz et al., 2000 ; Kaya et al., 2014 ; Gong et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%